Analysis Of Total Polyphenol Content Of Carrot Extract (Daucus Carota L.) Using The Folin-Ciocalteu Method - Wa Ode Nurani Arma; Rahmat Hidayat; Annie Rahmatillah (International Journal of Health Engineering and Technology, 2026)
Carrots (Daucus carota L.) are known to contain bioactive compounds, particularly phenolic compounds, which act as antioxidants. Objective: This study aimed to determine the total polyphenol content in carrot ethanol extract and evaluate its potential as a natural antioxidant source. This study was a quantitative experimental laboratory study. Carrot simplicia was obtained through a process of sorting, washing, chopping, drying, and grinding, then extracted using 70% ethanol solvent. The total polyphenol content was determined using UV-Vis spectrophotometry with Folin-Ciocalteu reagent and gallic acid as a standard, and the results were expressed in mg Gallic acid equivalent per gram of extract (mg GAE/g). Results: Gallic acid solution was used to obtain a standard curve. The analysis results showed a linear regression equation of y = 0.0161x + 0.042, R2 = 0.9947, with a correlation coefficient (r) value of 0.997. The total phenol content of each sample was determined with three replications. The results showed that carrot ethanol extract had a total polyphenol content of 42,205 mg GAE/g extract. This value indicates that carrot extract contains polyphenol compounds that have the potential to be a source of natural antioxidants.